(untitled) (World Bulletin of Public Health, 2022)
X-ray radiological features of 224 patients with severe COVID-19 were studied. The aim of the study was to study the radiological features of patients with a severe degree of COVID-19 against the background of complex treatment. The study revealed that patients with COVID - 19 associated pneumonia have their own characteristics of the course both in clinical, laboratory and radiological picture. All of the above radiological features of the course of COVID - 19 associated pneumonia in clinical practice are important for the differentiation of patients with purulent surgical inflammatory diseases of the lungs, bacterial etiology. Which inevitably positively affects the quality of treatment of patients with both purulent-surgical lung diseases and COVID-19 associated pneumonia